Suture approximation of esophageal atresia leads to esophageal recanalization - Patricio Galvez - Salazar; Luis M Figueroa - Gutierrez; Jorge Solarte - Henao; Jose L Castillo - Clavijo; Cristobal Abello; Juan C Dueñas - Ramirez (Elsevier, 2022)
Esophageal atresia is a congenital pathology in 1:4000 live newborns, which can occur isolated, associated with tracheoesophageal fistula or long gap (>2 vertebral bodies); the surgical objective is the ligation of the fistula and the esophageal anastomosis in the same surgery. However, this may not be possible in all cases [1]. The staged approach initially begins with the ligation of the tracheoesophageal fistula and gastrostomy, and definitive surgery focuses on the esophageal anastomosis. It is performed when the patient presents adequate clinical and anatomical conditions. Spontaneous recanalization of esophageal atresia is rare. The exact mechanism by which it occurs is unknown. Gastric reflux, being in contact with the esophageal distal end, generates inflammation and erosion of the wall, producing communication between the esophageal segments. We propose approximating the proximal and distal esophageal segments utilizing sutures produces an inflammatory process due to a foreign body generating a fistulous tract between the two esophageal components and esophageal recanalization [2]. We present two cases of esophageal recanalization to describe the clinical presentation, diagnostic and therapeutic approaches through imaging tests and endoscopy, contributing to the management of this unusual condition.